Liberalization of the Capital Account : Experiences and Issues - Rojas-Suarez, Liliana (Occasional Papers; Occasional Paper ;, 1993)
This study explores the industrial and developing countries use of capital controls since World War II, including their rationales for using them, and describes their experiences with relaxing controls as part of broader liberalization and structural reform efforts. The papers also outlines the potential medium-term costs and benefits of an open capital account and the policy measures that would help sustain capital account convertibility.